2022
DOI: 10.1007/s40259-022-00573-3
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Co-Stimulatory Receptors of the TNF Superfamily for Cancer Immunotherapy

Abstract: The clinical approval of immune checkpoint inhibitors is an important advancement in the field of cancer immunotherapy. However, the percentage of beneficiaries is still limited and it is becoming clear that combination therapies are required to further enhance the treatment efficacy. The potential of strategies targeting the immunoregulatory network by "hitting the gas pedal" as opposed to "blocking the brakes" is being recognized and intensively investigated. Hence, next to immune checkpoint inhibitors, agon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…Given FcyRIIB-mediated inhibition of ADCC, minimal to no engagement to inhibitory FcyRs should be strived at. Alternative approaches to enhance co-stimulatory receptor multimerisation could still consist of biAbs or state-of-the-art Fc-coupled fusion proteins ( 240 ). Moreover, adequate dosing regimen should be determined for patients taking in situ TIL activation status into account.…”
Section: Future Application Of Ics-mediated Agonistic Abs In Plc Mana...mentioning
confidence: 99%
“…Given FcyRIIB-mediated inhibition of ADCC, minimal to no engagement to inhibitory FcyRs should be strived at. Alternative approaches to enhance co-stimulatory receptor multimerisation could still consist of biAbs or state-of-the-art Fc-coupled fusion proteins ( 240 ). Moreover, adequate dosing regimen should be determined for patients taking in situ TIL activation status into account.…”
Section: Future Application Of Ics-mediated Agonistic Abs In Plc Mana...mentioning
confidence: 99%
“…The exploration and deployment of therapeutics targeting Tregs are extensive, chiefly because these cells express an array of receptors on their surface. The most utilized are agonists of the TNFR superfamily and antagonists of immune checkpoint inhibitors ( 230 , 231 ). These modulators alleviate autoimmune conditions and bolster anti-tumor responses by influencing Treg function.…”
Section: Potential Of Treg-based Immunotherapymentioning
confidence: 99%
“…While limited studies have been conducted to investigate the role of DNA methylation as a predictive biomarker in HNSCC, several recent studies suggested DNA methylation as a potential predictive biomarker in HNSCC particularly in immunotherapy. The tumor necrosis factor receptor superfamily members 4 (TNFRSF4, OX40) and 18 (TNFRSF18, GITR, AITR) have been under investigation as potential targets for the immunotherapy of various cancers, including HNSCC [49,50]. A study by Loick et al [49] investigated a detailed description of the DNA methylation landscape within GITR and OX40 (both located in close proximity on chromosome 1 p36.33 in HNSCC) [49].…”
Section: Role Of Dna Methylation Profiles In Relation To Response In ...mentioning
confidence: 99%